POLICE EFFECTIVENESS AND MILITARY INVOLVEMENT IN INTERNAL SECURITY OPERATIONS IN NIGERIA. - Obasi francis eze, (IJRDO - Journal of Social Science and Humanities Research, 2020)
Security of life and property are primary purpose of the Government. The Government through the Nigeria Police fulfils its obligation of security to the Nation. However, in recent times the Military has been involved in internal security operations. The study focuses on the police effectiveness and military involvement in internal security operations in Nigeria. To better under study this, I anchor the theoretical frame work on the relative deprivation theory of Blau & Blau. The theory states that men are most inclined to aggression when subjected to sustained and unjustified frustration and this potential for collective violence varies strongly with the intensity and scope of relative deprivation among members of groups. This theory is relevant to this study because it underscores the underlining causes of violence in the society. The research methodology adopted exploratory and explanatory approach while questionnaire and personnel observation were used in retrieving required data from the public.125 respondents were selected randomly from two main groups namely: Government officials and private individuals, simple percentages were used to analyze the data and also chi-square method was used in solving the hypothesis. The reliability coefficient for police effectiveness and military involvement in internal security participation questionnaire (PEMIISPAQ) was found to be positive. Four research questions and four hypotheses were raised in the study. The findings reveal that inadequate equipment, inadequate training, inadequate welfare, inadequate funding, and lack of community base policing are the root causes of police incapability to combat internal security operations in Nigeria. The study recommends that the effort of the Nigeria police alone cannot curb the rate of insecurity in the Nation and the military should remain an indispensable partner in internal security operations in the country.